A Note on Maximization Criteria - Hildreth, Clifford (Quarterly Journal of Economics, 1946)
Journal Article A Note on Maximization Criteria Get access Clifford Hildreth Clifford Hildreth Iowa State College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 61, Issue 1, November 1946, Pages 156–164, https://doi.org/10.2307/1882407 Published: 01 November 1946